PENGUKUHAN NILAI DAN PROFESIONALISME DI KALANGAN PENJAWAT AWAM KE ARAH EFEKTIF GOVERNAN DI MALAYSIA - Syed Ismail, Sharifah Hayaati; Ab Rahman, Asmak; Mohd Zain, Mohd Izani (Jurnal Syariah, 2009)
Professionalism is one of many elements that is crucial in ensuring quality public services which in turn is important in ensuring good governance. To protect the public welfare, this professionalism should be practiced by the government, politicians, corporate and public entities as a whole. This value has been given serious attention in Malaysia delivery system in order to meet public satisfaction. Public interest and satisfaction are major focus towards producing effective and good governance in a country. The article shows that corruption is one of the consequences when professionalism is not practiced in civil service. To prove it, this study utilises the documentation and content analysis as its methodology. Results of this study revealed that professionalism is a vital value and characteristic that leads to effective administrative governance. It is abundantly clear that any modern practice will apply the value of quality in public services and delivery to avoid maladministration including corruption. The same notion is shared and encouraged in Islamic teaching. Therefore, civil servant has no choice but to embrace values in order to practice professionalism.